Faculty competence in online teaching: Basis for a training design towards distance education - Ladwingon, Ruth Ladip; Gavino, Zorayda Calaycay; Valdez, Angeline Badong; Bangat, Rodemelia Bustamante; Baggas, Eunice Wacdagan (International Journal of Innovative Research and Scientific Studies, 2025)
This study assessed faculty members' online teaching competencies across technical, administrative, and pedagogical domains, prompted by the COVID-19 pandemic's shift to flexible learning. A survey questionnaire measured competence levels, with ANOVA and Chi-square tests analyzing differences among faculty grouped by age and teaching experience. Results revealed generally high competence across all three areas, yet pinpointed specific indicators needing further training and development. Significantly, senior faculty demonstrated lower competencies than younger colleagues. This underscores the need for targeted professional development programs to enhance online teaching skills, specifically addressing the needs of faculty based on age and experience. Such programs are crucial to ensuring all faculty are equipped for effective online instruction, thereby maximizing the success of flexible learning initiatives. The identified areas for improvement will inform the design of these targeted interventions, leading to more effective and equitable online learning experiences for all students.